Effect of heat treatment on quality of feed additive using tomato pomace - Єгоров, Богдан Вікторович; Малакі, Ілона Савелівна (Eastern-European Journal of Enterprise Technologies, 2014)
Rapid development of the poultry industry requires solving such problems as expanding the resource base and using alternative sources of raw materials, reducing manufacturing cost of animal feed products and ensuring calcium deficiency in highly productive layers. However, during the production of canned vegetables, there are large amounts of waste in the form of tomato pomace, which are very perishable and require immediate disposal. Therefore, a necessary condition for the development of the poultry industry is to elaborate a method of producing a feed additive using the by-products of the canning industry. The aim of the research is to study the effect of heat treatment, namely the extrusion process on the physicochemical properties and quantitative-qualitative composition of the feed additive microflora using tomato pomace. It is found that the extrusion process not only does not affect the feed additive quality, but also significantly improves the physical properties, increases the digestibility of nutrients by enzymes of the gastrointestinal tract of birds, and considerably enhances the sanitary properties of the additive. During extrusion, the content of solid starch in the feed additive decreases by 33.4% and the amount of water-soluble carbohydrates increases 5 times, which greatly improves its absorption by the body of birds. Conducting the extrusion process has allowed to reduce moisture content in feed additive by 34.5%, which is positive in terms of the perspective of its further processing and storage. In addition, under high temperature and pressure, the total amount of bacteria has decreased by 89%, and mycelium fungi - by 83%, which allows to count on the efficient storage of feed additive and use in the manufacture of animal feeds for poultry. The obtained feed additive will allow to solve the problem of disposal of tomato wastes, and the developed method of their processing will be less expensive as compared to the existing ones. Since the extrusion process is less energy-intensive, using the tomato pomace as a mixture humidifier before extrusion reduces the humidification costs.